2008
DOI: 10.1262/jrd.19150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Centrifugation Treatment before Vitrification on the Viability of Porcine Mature Oocytes and Zygotes Produced In Vitro

Abstract: Abstract. The aim of the present study was to investigate the effects of centrifugation pretreatment on the viability and nuclear status of porcine in vitro matured (IVM) oocytes and on the developmental competence of in vitro fertilized (IVF) oocytes (zygotes) after cryopreservation by vitrification (Solid Surface Vitrification; SSV). Mature oocytes having the first polar body after IVM and zygotes having the second polar body at 10 h after IVF were centrifuged at 10,000 × g at 37 C for 20 min and then subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…To our knowledge, these are the first piglets obtained from vitrified zygotes. Recently, our group reported for the first time the use of a modified SSV system for the successful cryopreservation of porcine zygotes (selected by the presence of a second polar body), which developed in vitro to the blastocyst stage; however, only a low percentage (5%) of these vitrified zygotes reached the blastocyst stage [43]. Here, we report an improved (approximately 15%) rate of in vitro blastocyst formation after vitrification of zygotes.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…To our knowledge, these are the first piglets obtained from vitrified zygotes. Recently, our group reported for the first time the use of a modified SSV system for the successful cryopreservation of porcine zygotes (selected by the presence of a second polar body), which developed in vitro to the blastocyst stage; however, only a low percentage (5%) of these vitrified zygotes reached the blastocyst stage [43]. Here, we report an improved (approximately 15%) rate of in vitro blastocyst formation after vitrification of zygotes.…”
Section: Discussionmentioning
confidence: 74%
“…Nevertheless, for decades there had been no reports of the cryopreservation of zygotes in livestock species, such as cattle and pigs. Recently, our group was the first to report the in vitro production of blastocysts from IVP porcine zygotes cryopreserved by solid surface vitrification (SSV) after visualization of the pronuclei by centrifugation [43]. The question remains, however, as to whether vitrified zygotes can develop to term, because the cryopreservation procedure might alter important processes such as DNA synthesis, which occurs at the pronuclear stage [44].…”
Section: Introductionmentioning
confidence: 99%
“…Other measures, such as induction of osmotic stress (by exposure to NaCl) has shown to improve developmental competence after vitrification (Lin et al 2008). Centrifugation (lipid depot relocation) for vitrification appears detrimental for in vitro-matured oocytes, but not in zygotes or later stages (Somfai et al 2008) Vitrification of in vivo-developed, ZP-intact pig embryos, where lipids were polarized by centrifugation of the blastomeres, by delipation and/or treatment with cytochalasin for cytoskeleton stabilization, has resulted after rewarming and ET, in piglets (Dobrinsky 1997, Dobrinsky et al 2000, Kobayashi et al 1998, Berthelot et al 2000, Cameron et al 2000. Blastocysts were also developed by in vitro fertilization (IVF) of follicular oocytes vitrified as cumulus-oocyte complexes from offal porcine follicles (Somfai et al 2010).…”
Section: Cryopreservation Of Oocytes and Embryosmentioning
confidence: 99%
“…Use of alternative methods such as vitrification instead of slow cooling led to better survival (see Massip 2001) including the birth of offspring (Berthelot et al 2000). However, large variation was seen among methods, sources and laboratories (Holm et al 1999, Cuello et al 2007, Somfai et al 2008, Ogawa et al 2010, including the method used for intrauterine deposition (Rodriguez-Martinez 2007b.…”
Section: Introductionmentioning
confidence: 99%
“…Otoi et al (1997) found that although centrifugation has a negative effect on bovine oocytes, its use is advantageous in the context of cryopreservation. A recent study with pig oocytes and embryos (Somfai et al, 2008) showed that centrifugation (10 000 g for 20 min) reduced the rate of surviving vitrified oocytes, although the proportion of parthenogenetic divisions was similar in the group of centrifuged and non-centrifuged oocytes (42 and 47%, respectively). Meanwhile, although zygote centrifugation slightly improves their survival after cryopreservation, it does not increase the developmental competence of surviving zygotes.…”
Section: Addition Of Cholesterol or Liposomesmentioning
confidence: 93%